Inhibition of CO2 corrosion of carbon steel with 1% Cr - Paolinelli, Luciano Daniel (2012)
One of the most employed methods for CO2 corrosion control in oil and gas production and transportation industry is the use of carbon and low alloy steels in conjunction with corrosion inhibitors. The inhibitor performance can be influenced by the microstructure and chemical composition of the steel. In previous works, it was shown that 1% Cr addition to carbon steel decreased the protectiveness of a commercial imidazoline-based inhibitor. However, it was suspected that changing the flow rates may modify the inhibitor behaviour. In the present work, the performance of an imidazoline-based inhibitor was investigated on two carbon steels one with the other without 1% Cr, under different flow rates. Corrosion and corrosion inhibition experiments were carried out using a rotating cylinder electrode at different rotation speeds in a deoxygenated 5 wt.% NaCl CO2-saturated solution at 40 °C, pH 6 with and without inhibitor addition. Electrochemical measurements were taken during each experiment and sample surfaces were analyzed after each experiment. Inhibitor performance was found to be dependent on flow velocity and chemical composition of carbon steel.